Comprehensive Physiology 2020
DOI: 10.1002/cphy.c190016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Regulation of Transporters of Amino Acid Absorption in Inflammatory Bowel Diseases

Abstract: Intestinal absorption of dietary amino acids/peptides is essential for protein homeostasis, which in turn is crucial for maintaining health as well as restoration of health from significant diseases. Dietary amino acids/peptides are absorbed by unique transporter processes present in the brush border membrane of absorptive villus cells, which line the entire length of the intestine. To date, the only nutrient absorptive system described in the secretory crypt cells in the mammalian intestine is the one that ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 148 publications
0
5
0
Order By: Relevance
“…Glutamine is the primary metabolic fuel for intestinal enterocytes. It is now considered a “conditionally essential” amino acid as compared to the prior paradigm of a non-essential amino acid [ 38 ]. Glutamine is assimilated in villus cells through a sodium dependent co-transport process in the BBM specifically via B0AT1.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is the primary metabolic fuel for intestinal enterocytes. It is now considered a “conditionally essential” amino acid as compared to the prior paradigm of a non-essential amino acid [ 38 ]. Glutamine is assimilated in villus cells through a sodium dependent co-transport process in the BBM specifically via B0AT1.…”
Section: Discussionmentioning
confidence: 99%
“…Na + ‐glutamine cotransporter B 0 AT1 in villus cells was inhibited secondary to reduced cotransporter numbers and reduced NKA activity. SNAT5/SN2 in crypt cells was stimulated secondary to increased transporter affinity and NKA activity 98 . LTD4 has been shown to stimulate SN2‐mediated glutamine uptake in chronic enteritis.…”
Section: Electrolyte Transport Regulates Intestinal Nutrient Absorpti...mentioning
confidence: 95%
“…SNAT5/SN2 in crypt cells was stimulated secondary to increased transporter affinity and NKA activity. 98 LTD4 has been shown to stimulate SN2‐mediated glutamine uptake in chronic enteritis. Then Niraj Nepal et al found that LDT4 elevated [Ca 2+ ] i through leukotriene receptors, stimulating NKA in intestinal crypt cells via the PKC pathway.…”
Section: Electrolyte Transport Regulates Intestinal Nutrient Absorpti...mentioning
confidence: 99%
“…To investigate the mechanisms of the LP diet that affect amino acid absorption, additional measurements were done on the mRNA expression of small peptides and free amino acid transporters in response to the availability of dietary amino acids. The small intestine is the primary site for the absorption of short peptides or amino acids, and amino acids and peptide transporters mediate its absorption and transport processes, respectively (Soudamani et al, 2020). Different amino acid transporters have unique substrate specificity (Wu, 2021).…”
Section: Notementioning
confidence: 99%